Commentary: Communicating in crisis: Reflections, opportunities, and challenges for healthcare communication in the COVID-19 pandemic - Edmonds, David Matthew; Zayts-Spence, Olga; Alder, Katharine (Qualitative Health Communication, 2022)
Background: The coronavirus disease 2019 (COVID-19) pandemic has changed how healthcare professionals, patients, and relatives communicate with each other. Aim: We take stock of the current state of affairs in healthcare communication research amid the continuing pandemic. We draw upon our expertise as communication researchers and clinical experience as a medical professional working in the pandemic to reflect upon the challenges and opportunities that the pandemic has created for healthcare communication research and practice. Findings: We explore five topics of importance for research on healthcare communication during COVID-19 and its aftermath. First, we discuss how the ‘epistemics’ of COVID-19 are navigated in patients’ communication with doctors. Second, we elaborate on the problems in communicating the prognostic uncertainty of COVID-19. Third, we consider online COVID-19 support groups as an important site for investigating the pandemic’s multi-dimensional impacts. Fourth, we consider the challenges of the shift from face-to-face to video-mediated healthcare service provision. Fifth, we explore how fast-tracking graduate medical students into the workforce left them feeling unprepared for the communicative demands of such work. Conclusion: We call for direct collaboration between medical professionals and healthcare communication researchers to utilize evidence-based findings to solve the communicative demands posed by the pandemic. Collaboration and research need to be adaptive to the dynamic nature of the pandemic.